"Uberizing" home care in Ontario. Issue 4 (July 2016) - Wojtak, Anne; Stark, Linda
This article looks at home care in Ontario and its role as a foundation for a sustainable healthcare system in the future. Beginning with the history and evolution of the service delivery model, it examines current challenges and opportunities to unleash the potential of home care within a more integrated model for patient-centred care for the future. An in-depth look at how to better coordinate, integrate, and fund care for patients is highlighted.